2022
DOI: 10.1101/2022.05.05.490836
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal analysis suggests a reciprocal relationship between 3D chromatin structure and transcription

Abstract: To infer potential causal relationships between 3D chromatin structure, enhancers, and gene transcription, we mapped each feature in a genome-wide fashion across eight narrowly-spaced timepoints of macrophage activation. Enhancers and genes connected by loops exhibited stronger correlations between histone H3K27 acetylation and expression than can be explained by genomic distance or physical proximity alone. Changes in acetylation at looped distal enhancers preceded changes in gene expression. Changes in gene … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 74 publications
(115 reference statements)
5
5
0
Order By: Relevance
“…Interestingly, 93% (75 out of 81) of gained loops that overlapped a differential gene promoter showed the same direction of change as the gene (p = 2.91 × 10 −16 , binomial test) ( Fig 2C ). This is consistent with our previous work in macrophages 30,31 and suggests that gained loops are relevant in increasing transcription of genes at their anchors. Upregulated genes found at the anchors of gained loops include TGFB1 and THBS1 , both of which are megakaryocyte-related 32,33 .…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Interestingly, 93% (75 out of 81) of gained loops that overlapped a differential gene promoter showed the same direction of change as the gene (p = 2.91 × 10 −16 , binomial test) ( Fig 2C ). This is consistent with our previous work in macrophages 30,31 and suggests that gained loops are relevant in increasing transcription of genes at their anchors. Upregulated genes found at the anchors of gained loops include TGFB1 and THBS1 , both of which are megakaryocyte-related 32,33 .…”
Section: Resultssupporting
confidence: 93%
“…In contrast, lost loops that overlapped a differential gene promoter showed no such concordant behavior, with only 33% (15 out of 45) exhibiting the same directional change as the gene (p = 0.04, binomial test) ( Fig 2C ). These findings again agree with our previous work in macrophages 30,31 , where we did not see a significant decrease in expression of genes at lost loop anchors, suggesting that loss of looping is not sufficient to decrease transcriptional output 30,31 . This is also consistent with work by Rao et al that found almost no change in gene transcription following virtually complete abrogation of loop-extrusion 14 .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These opposing findings have implications for our understanding of how certain factors act on distinct regulatory elements such as enhancers and promoters to orchestrate cell type-specific gene expression. Some mechanisms suggest chromosome looping may mediate enhancer-promoter contacts and could be correlated with gene activity ( Palstra et al, 2003 ; Vernimmen et al, 2007 ; Rao et al, 2014 ; Bonev et al, 2017 ; Freire-Pritchett et al, 2017 ; Ghavi-Helm, 2020 ; Oudelaar et al, 2020 ; Oudelaar and Higgs, 2021 ; Reed et al, 2022 ). Interestingly, a recent study suggests that distinct regulatory sequences, termed tethering elements, could mediate distal enhancer-promoter contacts and determine activation dynamics ( Batut et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%